iREPORT / Siti Nur Aqilah Mohd Kassim … [et al.] - Mohd Kassim, Siti Nur Aqilah; Wan Mohd Sarafi, Wan Umi Yusyaradiya; Mohd Khairul Afikin, Nur Khaleysa Ariana; Mohamad Azan, Muhammad Afiq Irfan; Yahya, Rajuta (Faculty of Computer and Mathematical Sciences, 2021)
i-report System is a system for the school prefects to send daily duty reports to the school managements, discipline teacher and school discipline secretary virtually. This system will facilitate the school managements to keep track of disciplinary problems at school effectively and instantly. This system also enables the school prefects to share their reports among each other individually or as a whole group. The use of this system enables the school prefects to remain anonymous when making reports of any disciplinary problems. The reports filed by the school prefects will be saved in a database. Consequently, i-report will help in reducing disciplinary problems at school.